Masculinity, power and intersectionality - Christensen, Ann-Dorte (Politica, 2019)
Studies on men and masculinity focus on men’s identities and values, and on the normative, accepted cultural practice of being a man in a specific context. This research field has contributed significantly to gender studies and has produced new knowledge, which is useful for the social sciences in general, for instance in terms of understanding processes of social differentiation and political values. Theoretically, studies on men and masculinities have been dominated by the theory of hegemonic masculinity and a focus on patriarchal power structures. The article introduces an intersectional approach as a fruitful alternative in studies of the complexities and ambiguities of gendered identities, inequalities and power structures. The intersectional argument is illustrated by two empirical examples: 1) men as the extreme gender at the top and bottom of society, and 2) new masculinity ideals.